The Post-2015 Institutional Shock in Poland: Some Empirical Findings - Tadeusz Kowalski (CESifo Forum, 2021)
The aim of this article is to discuss and assess the post-2015 institutional environment in Poland. As early as December 2015, the newly elected conservative President and the parliamentary majority began to implement their vision of the state. It included a new law-making culture and an overhaul of the judicial system. These changes were supplemented by a sweeping nomenclature in public institutions and state-controlled companies. The new political establishment took full control of public media. The analyses are focused on the institutional shock to the judicial system. The changes are studied through the prism of manager perceptions of the practices of public institutions, law-making and law-enforcement. The primary data were collected annually with the use of surveys conducted on a carefully selected group of middle and high-level managers with a university degree. The picture of 2016-2018 derived from the survey is analyzed and compared with earlier years. There was not only a lack of significant improvement in the main areas of interest of the coalition but in many cases, it deteriorated. Particularly noteworthy is the general perception of increased uncertainty in all the institutional spheres analyzed in the article.
Keywords: 330